2012
DOI: 10.1016/j.yexmp.2012.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus modulates HIVAN phenotype through inhibition of epithelial mesenchymal transition

Abstract: HIV-associated nephropathy (HIVAN) is characterized by proliferative phenotype in the form of collapsing glomerulopathy and microcystic dilatation of tubules. Recently, epithelial mesenchymal transition (EMT) of renal cells has been demonstrated to contribute to the pathogenesis of proliferative HIVAN phenotype. We hypothesized that sirolimus would modulate HIVAN phenotype by attenuating renal cell EMT. In the present study, we evaluated the effect of sirolimus on the development of renal cell EMT as well as o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
(76 reference statements)
1
13
0
Order By: Relevance
“…Our previous studies have implicated several pathways that are involved in the pathogenesis of HIVAN, e.g., epithelial mesenchymal transition (EMT) was demonstrated to contribute to the proliferative phenotype of HIVAN (Yadav et al, 2010; Yadav et al, 2012). Tg26 mice showed enhanced renal tissue expression of ZEB2 and diminished expression of E-cadherin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies have implicated several pathways that are involved in the pathogenesis of HIVAN, e.g., epithelial mesenchymal transition (EMT) was demonstrated to contribute to the proliferative phenotype of HIVAN (Yadav et al, 2010; Yadav et al, 2012). Tg26 mice showed enhanced renal tissue expression of ZEB2 and diminished expression of E-cadherin.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact mechanisms which contribute to the pathogenesis of HIVAN are not clear. Studies conducted in our laboratory demonstrated that epithelial-mesenchymal transition (EMT) in renal epithelial cells could contribute to the development of proliferative phenotype in HIV-1 transgenic mice (Tg26), the most commonly used mouse model of HIVAN (Kopp et al, 1992; Yadav et al, 2010; Yadav et al, 2012). In addition, mammalian target of rapamycin (mTOR) pathway was activated in HIVAN mice (Kumar et al, 2010; Rehman et al, 2012; Nicoletti et al, 2011).…”
mentioning
confidence: 99%
“…Recently, the role of mammalian target of rapamycin (mTOR) pathway has been demonstrated in the progression of in HIVAN [16]. Rapamycin, an inhibitor of mTOR pathway, not only inhibited the activation of the mTOR pathway but also attenuated the development of proliferative phenotype in HIVAN [35]. …”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that miR-200 can be involved in the progression of HIVAN. In addition, rapamycin has been demonstrated to modulate HIV transcription as well as attenuation of the proliferative phenotype of HIVAN through inhibition of epithelial mesenchymal transition (EMT) in renal cells [35]. However, the contribution of rapamycin to miRNA expression in HIVAN and their potential role in the pathological processes has not been investigated to date.…”
Section: Introductionmentioning
confidence: 99%
“…One cannot change the genetic background; however, one can control the environmental factors and also modulate the host factors. Recently, the role of mammalian target of rapamycin (mTOR) pathway has been demonstrated in the development of proliferative phenotype in HIVAN (14); rapamycin (sirolimus) not only inhibited the activation of the mTOR pathway but also attenuated the development of proliferative phenotype in HIVAN (15). In addition, rapamycin has been reported to modulate HIV infection.…”
mentioning
confidence: 99%